Análise do Programa Nacional de Alimentação Escolar no município de Dom Pedrito - Jarosezwski, João Carlos Prerniska (2020)
This work has as main objective to analyze the main difficulties faced in the city of Dom Pedrito for the execution of the National School Feeding Program (PNAE), both from the point of view of public managers and from the perspective of local family farmers. This program, instituted by Law no. 11,947, of 2009, stipulates that, at least, 30% of the PNAE's resources are destined for the purchase of products from local family farming. In methodological terms, the study can be classified as qualitative in terms of its approach, applied in terms of its nature and exploratory and descriptive in terms of its objectives. Considering these definitions, the collection was carried out in a bibliographic and documentary way to obtain secondary data. For the collection of primary data, semi-structured interviews were applied to public agents and family farmers. As for the results, it was observed that some obstacles are known by both categories, such as the difficulty of access that producers have to deliver their goods in the urban area, from the necessary distances to travel to the conditions of the rural roads in the municipality. The split in delivery and the need for other forms of subsidy for rural producers also proved to be difficult for the good performance of the PNAE, as well as the lack of documentation on the part of some farmers. Other difficulties are related to the insufficient production of food needed by municipal schools and climatic conditions, when taking into account the rains, droughts and bad weather. From the point of view of city hall managers and also from EMATER, forms of financing for farmers are necessary, either through the strengthening of existing policies, or through new forms of public financing, in addition to the need for improvements in infrastructure and food delivery logistics in municipal schools. From this, it was found the absence of joint planning for production adapted to the needs of municipal schools and rural producers. For this, it is necessary to map production and align with the needs of municipal schools.